Humanistic health of the physical living environment: The equity of property inheritance in China - Mengrong Shu; Jinxin Li; Yuhan Wu; Kaida Chen; Kaida Chen; Shuhui Ding (Frontiers Media S.A., 2023)
Equity in the inheritance culture of family property is an important component of humanistic health in modern living environments. The inheritance of property under Chinese traditional family culture is the material basis for the continuation of family and clan. This study demonstrates the equity component embedded in traditional family inheritance culture and further studies of the healthy human settlements environment. Based on the theory of "equal share for all sons" in ancient China and the "equity" and "justice" that are of modern significance, this paper analyzes the family division culture of individual traditional housing and the corresponding impact indices of family division equity. Taking Renhe Village, a typical local residential building of the middle and late Qing Dynasty as the research object, this study built a spatial syntax data model and 3D simulation technology for the simulation analysis of space and climate. The results show that Renhe Village meets the requirements of the equity evaluation system of housing property rights distribution in terms of the natural unit indicator (quantity, lighting, ventilation) and the overall spatial indicator (privacy, centrality, convenience). In other words, equity does not mean an absolute average share, but an equity culture formed after six evaluation indices under the subdivision of two indicators are balanced. Based on the above, an equity system model of housing property rights distribution was established, and the weight of the ancients' attention to the housing distribution standard was explored. It is further found that the ancients attached more importance to light among the natural unit indicators, and attached the most importance to centrality in the overall spatial indicators. These findings provide new ideas for understanding the equity of property inheritance under Chinese traditional family culture. They also provide quantifiable criteria for the distribution of modern rural housing and social security housing, and ultimately provide a reference for the humanistic public health of the modern living environment.